2021
DOI: 10.1108/ijoa-01-2021-2567
|View full text |Cite
|
Sign up to set email alerts
|

Organizational citizenship behavior for the environment: a management perspective

Abstract: Purpose This study aims to investigate the relationship between organizational citizenship behavior for the environment (OCBE) of managers and the constructs of the theory of planned behavior: perceived behavioral control (PBC) and attitude toward the environment. The current study also aims to explore the magnitude of this relationship with subjective norms as a moderating variable. Design/methodology/approach Data were sourced from a total number of 140 respondents (managers) from different firms in The Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
(95 reference statements)
1
1
0
Order By: Relevance
“…Meanwhile, there are few researches on the relationship between leaders and green product Second, organizational citizenship behavior toward the environment plays a mediating role between green transformational leadership and green product innovation. This study helps enterprises to clarify the importance of green environmental behavior of employees in the organization, similar results were also found by Daily et al [40], Akterujjaman et al [58]. In the work environment, learning among employees enables organizations to overcome the boundaries of existing knowledge resources [42].…”
Section: Discussionsupporting
confidence: 83%
“…Meanwhile, there are few researches on the relationship between leaders and green product Second, organizational citizenship behavior toward the environment plays a mediating role between green transformational leadership and green product innovation. This study helps enterprises to clarify the importance of green environmental behavior of employees in the organization, similar results were also found by Daily et al [40], Akterujjaman et al [58]. In the work environment, learning among employees enables organizations to overcome the boundaries of existing knowledge resources [42].…”
Section: Discussionsupporting
confidence: 83%
“…Employees' pro-environmental behavior, called Organizational Citizenship Behavior towards the Environment (OCBE), is an individual voluntary action that leads to environmental performance in an organization from employees (Anwar et al, 2020). This is similar to previous research from (Luthfi & Nawangsari, 2021), (Sunaris et al, 2022), (Akterujjaman et al, 2021), which stated that Organizational Commitment had no positive effect on OCBE.…”
Section: Discussion and Implicationsupporting
confidence: 77%
“…Our literature search identified only one cross-sectional study that reported evidence consistent with this proposition. Specifically, Akterujjaman et al (2022) showed that the relation between perceived behavioral control and managers’ organizational citizenship behavior for the environment was stronger when subjective social norms were high.…”
Section: Integrative Conceptual Model Of Leadership and Environmental...mentioning
confidence: 99%